1998
DOI: 10.1094/pdis.1998.82.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus Infection and Aflatoxin Accumulation in Resistant and Susceptible Maize Hybrids

Abstract: Field studies were conducted for 2 years in Mississippi to monitor maize kernel infection and aflatoxin accumulation caused by Aspergillus flavus at various times during the growing season. Hybrids resistant and susceptible to A. flavus were compared to determine temporal differences in infection and aflatoxin levels. The resistant hybrids tested were Mo18W × Mp313E, Mp420 × Tx601, and SC54 × SC76; and the susceptible hybrids tested were GA209 × Mp339, Mp307 × Mp428, and Mp68:616 × SC212M. The top ear of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Germplasm screening studies have identified a number of public sources associated with lower levels of aflatoxin production (Thompson et al 1984;Darrah et al 1987;Widstrom et al 1987;Zummo 1988, 1990;Campbell and White 1995a;Windham and Williams 1998). However, levels of aflatoxin production have not been adequate in commercial hybrids, especially in years with environmental condtions where aflatoxin production is favored (Payne 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Germplasm screening studies have identified a number of public sources associated with lower levels of aflatoxin production (Thompson et al 1984;Darrah et al 1987;Widstrom et al 1987;Zummo 1988, 1990;Campbell and White 1995a;Windham and Williams 1998). However, levels of aflatoxin production have not been adequate in commercial hybrids, especially in years with environmental condtions where aflatoxin production is favored (Payne 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, the combined effect is yet to be explored. In EU field trials the aflatoxin content of resistant maize cultivars will be compared to susceptible cultivars, which is expected to be lower than previously achieved 70% (Windham and Williams, 1998). The aflatoxin contents of maize (EU) and peanuts (China) after treatment with atoxigenic fungal strains will be compared to non-treated crops in field trials.…”
Section: Pre-harvest Impactsmentioning
confidence: 99%
“…flavus isolate NRRL 3357 has produced high levels of aflatoxin in maize grain in prior studies [25][26][27] and was used to increase the inoculum in these experiments. Inoculum was increased according to Windham et al [26].…”
Section: Fungal Inoculum and Aflatoxinmentioning
confidence: 99%